2007
DOI: 10.1002/jat.1221
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal toxicology: a strategy for assessment of functional toxicity to the adrenal cortex and steroidogenesis

Abstract: The adrenal is the most common toxicological target organ in the endocrine system in vivo and yet it is neglected in regulatory endocrine disruption screening and testing. There has been a recent marked increase in interest in adrenal toxicity, but there are no standardised approaches for assessment. Consequently, a strategy is proposed to evaluate adrenocortical toxicity. Human adrenal conditions are reviewed and adrenocortical suppression, known to have been iatrogenically induced leading to Addisonian crisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 100 publications
(123 reference statements)
1
58
0
1
Order By: Relevance
“…This approach was supported by its successful confirmation of known adrenergic agents, such as Dex and AG. The adrenal toxicity of simazine and PCB126 observed in this study might also reflect the effects reported previously (Harvey et al, 2007). The EC50 values of Dex, AG, simazine, and PCB126 for anterior pituitary POMC expression as determined in this study were significantly lower than their NOAECs (Table 1), which might also indicate the fact that the adrenal/interrenal gland is one of their primary targets with regard to endocrine disruption effects.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…This approach was supported by its successful confirmation of known adrenergic agents, such as Dex and AG. The adrenal toxicity of simazine and PCB126 observed in this study might also reflect the effects reported previously (Harvey et al, 2007). The EC50 values of Dex, AG, simazine, and PCB126 for anterior pituitary POMC expression as determined in this study were significantly lower than their NOAECs (Table 1), which might also indicate the fact that the adrenal/interrenal gland is one of their primary targets with regard to endocrine disruption effects.…”
Section: Discussionsupporting
confidence: 83%
“…These include simazine, PCB126, BADGE, and TCDD (Hinson and Raven, 2006;Hecker et al, 2006;Villeneuve et al, 2007;Harvey et al, 2007). To examine the effects of these chemicals on POMC:EGFP expression in our transgenic fish as well as endogenous POMC expression in zebrafish, Tg (POMC: EGFP) reporter fish and wild-type zebrafish were treated with those chemicals for 4 days starting at 1 dpf (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since synthesis of steroid hormones starts from cholesterol [1,7,10,15], the decrease in circulating testosterone in PaA-deficient animals probably results from a decrease in cholesterol synthesis induced by the PaA deficiency. This is also true for steroid hormone synthesis in the adrenal gland.…”
Section: Discussionmentioning
confidence: 99%